The Effectiveness of China’s Twitter Diplomacy in Defending its Sovereignty in Taiwan 2022 - Rahmawati, Ulfa; Surwandono, Surwandono (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2025)
This article analyses the effectiveness of digital diplomacy as a tool of Chinese political communication to manage international public opinion on the status of Taiwan. Using the concept of digital diplomacy and content analysis, the author analyses data sourced from tweets from the Chinese Ministry of Foreign Affairs Twitter account and five Diplomat accounts using the NVivo application to see the narratives formed and the public's response to the narrative. This study found that the Chinese government and diplomats framed the